Pełnomocność dziecka w edukacji wczesnoszkolnej w odsłonie krytycznych zdarzeń - Nowicka, Marzenna (Studia Edukacyjne, 2019)
The article presents the concept of empowerment in the context of early childhood education, mentioning its 5 dimensions, i.e. meaning, self-determination, competence, influence and security. Attempts to identify these dimensions are presented in the collected research material in the form of critical events from students’ pedagogical practices. In the light of the results obtained, early school education appears as an environment for blocking students’ empowerment in each of the highlighted aspects. The summary of the article identifies the possibilities of overcoming barriers in respecting the autonomy of a child at school.